Privilege and Extinguishment of the "subject" - Maria Inês Rosa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
We develop the issue of privilege in connection with the problem of "subject". Such problem is referrred to the language. Language is understood as a relationship to the other, the "subject". This relationship is never dual because it includes a third party. As such, the language, the word, implies and affects who utters it, to whom it has been addressed, and who has heard it. Words heard and addressed to the other referred to the academic environment, offered the opportunity for refflections on this issue. The analysis highligths the fact that words carry and [re]affirm the privilege and through privilege the place for the other is determined within the structure of social hierarchies and frontiers between the privileged and the non-privileged-"we" and "they"-are established. This lead, with respect to language as a relationship to the other, to the erasure of the "subject", with privilege taking its place.